2017
DOI: 10.1080/2162402x.2017.1356144
|View full text |Cite|
|
Sign up to set email alerts
|

Analysis of PD1, PDL1, PDL2 expression and T cells infiltration in 1014 gastric cancer patients

Abstract: Although immune checkpoint blockade have demonstrated promising results, their effects on gastric cancer (GC) are under investigation. Understanding the clinical significance of PD1 and its ligands' expression, together with T cell infiltration might provide clues for biomarkers screening in GC immunotherapy. Immunohistochemistry were performed on a tissue microarray including 1,014 GC specimens using PD1, PDL1 and PDL2 antibodies. T cell markers CD3 and CD8 were also stained and quantified by automated image … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
85
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 46 publications
8
85
0
1
Order By: Relevance
“…However, the relationship between PD-L1 expression and the prognosis remains controversial in GC. Many researches showed that PD-L1 expression had a negative impact on patient survival [24][25][26][27], but some studies indicated that PD-L1 positivity was associated with favorable outcomes [16,28]. In our study, PD-L1 expression in GC was related to some adverse clinicopathological characteristics, which was observed more frequently in advanced GCs occurred in the older patients and with bigger tumor size.…”
Section: Pd-l1 Expression In Gastric Cancermentioning
confidence: 49%
See 1 more Smart Citation
“…However, the relationship between PD-L1 expression and the prognosis remains controversial in GC. Many researches showed that PD-L1 expression had a negative impact on patient survival [24][25][26][27], but some studies indicated that PD-L1 positivity was associated with favorable outcomes [16,28]. In our study, PD-L1 expression in GC was related to some adverse clinicopathological characteristics, which was observed more frequently in advanced GCs occurred in the older patients and with bigger tumor size.…”
Section: Pd-l1 Expression In Gastric Cancermentioning
confidence: 49%
“…In our study, the positive expression of PD‐L1 was observed in 37.3% cases. PD‐L1 was detected in 15% to 75% of GC patients according to previous literatures . We suppose varied antibodies, different tissue handling methods, and evaluating systems used to define PD‐L1 positivity may all lead to such a wide range of distinct expression rates.…”
Section: Discussionmentioning
confidence: 92%
“…All patients had undergone adjuvant chemotherapy with capecitabine plus oxaliplatin (XELOX). The median number of chemotherapy cycles was 6 (range, [3][4][5][6][7][8][9][10][11][12]. Overall survival (OS) was defined as the time from surgery to death or the last follow-up.…”
Section: Dear Editormentioning
confidence: 99%
“…CCNB1 and CDK1 have been found to regulated drug sensitiveness not only through cell cycle pathway, but p53 pathway according to our analysis. Previous study also found that PCNA was associated with cancers development [22,23] and patients prognosis [24,25] .…”
Section: Discussionmentioning
confidence: 73%